2016
DOI: 10.1007/s10533-015-0177-1
|View full text |Cite
|
Sign up to set email alerts
|

Balancing watershed nitrogen budgets: accounting for biogenic gases in streams

Abstract: Denitrification is critical for removal of reactive nitrogen (Nr) from ecosystems. However, measuring realistic, scalable rates and understanding the role of denitrification and other dissimilatory processes in watershed nitrogen (N) budgets remains a significant challenge in biogeochemistry. In this study, we focused on the stream reach and network scale in three Mid-Atlantic coastal plain watersheds. We applied open channel methods to measure biogenic N 2 and N 2 O gas fluxes derived from both in-stream and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 86 publications
6
43
2
Order By: Relevance
“…Using separate microcosm estimates of ER and DN to partition their relative contributions, our results show that the water column may be responsible for a substantial portion of reach‐scale ER in some rivers, and a portion of water column N removal can be attributed to denitrification which permanently removes NO 3 − ‐N from the ecosystem. We note that the microcosm approach excludes the influence of groundwater on sediment DN, which can be substantial in small streams [ Gardner et al ., ] but likely less influential in our study rivers. Incorporating these findings into watershed models focused on N uptake or retention [ Alexander et al ., ; Wollheim et al ., ; Ye et al ., ] will improve the accuracy and mechanistic basis of these models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using separate microcosm estimates of ER and DN to partition their relative contributions, our results show that the water column may be responsible for a substantial portion of reach‐scale ER in some rivers, and a portion of water column N removal can be attributed to denitrification which permanently removes NO 3 − ‐N from the ecosystem. We note that the microcosm approach excludes the influence of groundwater on sediment DN, which can be substantial in small streams [ Gardner et al ., ] but likely less influential in our study rivers. Incorporating these findings into watershed models focused on N uptake or retention [ Alexander et al ., ; Wollheim et al ., ; Ye et al ., ] will improve the accuracy and mechanistic basis of these models.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that groundwater can also be out of equilibrium with the atmosphere due to groundwater flowing through soils at different temperatures than the river. Estimates of the groundwater contribution to excess N 2 and Ar can be made using 222 Rn to separate in‐stream and groundwater contributions to N 2 production, and recent research has shown that groundwater can make significant contributions to excess N 2 in headwater streams [ Gardner et al ., ]. We were unable to separate these contributions with our data, but we assumed that the importance of groundwater contributions to N 2 production decreases with increasing stream size, as has been shown for CO 2 [ Hotchkiss et al ., ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is necessary to know gas exchange using this method, even though the net flux of O 2 between stream and air is of little interest relative to the biological fluxes of O 2 in the stream. This method has been extended to other bioreactive gases, such as N 2 (Baulch, Venkiteswaran, Dillon, & Maranger, 2010;Gardner, Fisher, Jordan, & Knee, 2016). The second area of research interest is the source of streams as greenhouse gases to the atmosphere (Butman & Raymond, 2011;Raymond et al, 2013;Stanley et al, 2016), where gas exchange is needed to estimate gas flux following Equation 1.…”
mentioning
confidence: 99%
“…denitrified N 2 ) emitted in bubbles is that the fate of anthropogenic N will appear to be uncertain [13] [14] because nitrogen will seem to be "missing", in other words, not enough N output will be found to balance riverine N inputs and outputs. Several studies observed such imbalances [1] [11] [15]- [22].…”
Section: Introductionmentioning
confidence: 99%